Alchemilla vulgaris effects on egg production and quality expressed by heat-stressed quail during the late laying period - Akdemir, F.; Koseman, A.; Seker, I. (South African Journal of Animal Sciences, 2019)
Potential for mitigating effects of heat stress through dietary Alchemilla vulgaris (AV) supplementation during the late laying period of Japanese quail (Coturnix coturnix japonica) were investigated. A 2 x 3 factorial arrangement of environmental temperature (ET) regimes and levels of dietary supplementation with AV (0%, 1%, and 3%) was used in a 75-day experiment. Twenty-five quail were randomly assigned to each treatment with five replicate cages of five birds. The birds were housed in temperature-controlled rooms at 22 +/- 2 degrees C for 24 h/day (TN) or 34 +/- 2 degrees C between 09h00 and 17h00 followed by 22 +/- 2 degrees C for 16 h/day (HS). The interaction of ET and supplement regimes was rarely significant. In HS quail supplemented with 1% AV, egg production was reduced and FCR was increased compared with the other treatments. Dietary AV was found to reduce egg production in TN conditions, but 3% AV supplementation in the HS group prevented decreased egg production and improved FCR. Various indicators of egg quality were significantly affected by supplementation with AV at certain times during the experiment. Most effects of HS on egg quality were manifest in the first 15 days of ET regimes. Although HS significantly decreased eggshell weight until 31-45 days, AV supplementation improved it on the 45th day and then maintained it through the end of the experiment. Thus, AV may mitigate some effects of HS by partially preventing decreased egg production and increased FCR during the late laying period of Japanese quail.
Keywords: Coturnix coturnix japonica; flavonoids; supplement